The study of applying the three methods in forming Chinese character (三 书说) for the teaching Chinese as the third language at UiTM / Wong Hoong Cheong … [et al.] - Wong, Hoong Cheong; Lew, Ya Ling; Goh, Ying Soon; Yap, Soh Leay (Akademi Pengajian Bahasa, 2021)
Teaching non-native Chinese students to learn Chinese characters is one of the foundations of learning Chinese language, especially in learning Chinese as a foreign language or third language. However, it is actually one of the difficulties faced by instructors who are teaching Chinese as a foreign language. There are various ways to teach Chinese characters, if the instructors simply rely on the stroke scheme in the textbook, it will inevitably make the class dull and cause the students less interested in learning Chinese. The theory of Three Methods in Forming Chinese Character (三书说) is a theory to analyze the structure of Chinese characters and explain the rationales of the formation of Chinese characters. These non-Chinese students are able to learn the Chinese culture which are carried in these Chinese characters. The instructors should master the theory and concept of Three Methods of forming Chinese characters (三书说) to make the learning process fun. Moreover, by applying this theory can enable the non-native Chinese students to have a deeper understanding and also stimulate their interest in learning Chinese characters. This article will discuss and analysis the application of the theory and concept of the Three Methods of forming Chinese characters (三书说) in teaching the Chinese characters in the syllabus of UiTM third language courses in the hope of heightening the learning effect of Chinese character instruction as a whole.